Investigation on interfacial slipping response of laminated channel beams with bolt connections in modular steel buildings. (1st January 2023) - Xu, Bo; Xia, Junwu; Ma, Renwei; Chang, Hongfei; Yang, Chen; Zhang, Lihai
Abstract: It is well-known that interfacial slippage is a critical factor for the cooperation of laminated beams in modular steel buildings. However, the slipping behavior of laminated steel channel beams with bolt connections has not been fully understood. In the present study, a series of bending tests using the digital image correlation (DIC) optical measuring method, finite element (FE) parametric study, and theoretical derivation were conducted to investigate the interfacial slip response of laminated channel beams comprehensively. The results showed that the increase in bolt connection number significantly constrained the slipping behavior, while the effect of layer height ratio was comparatively not obvious. Moreover, the nonlinear improvement of anti-slip behavior by adding interfacial bolt connections was observed, which suggested that the appropriate bolt number should be adopted in engineering practice for optimal efficiency. The analytical models provided a reliable assessment for the interfacial slippage, and laid a foundation for further theoretical study on the cooperative bending behavior of laminated channel beams. Highlights: Laminated beams with varying bolt numbers showed different load-slip mechanisms. The appropriate bolt number should be adopted for optimal engineering efficiency. The analytical procedure gave good prediction of slip regarding design parameters.